Modeling Air Entrainment Rate and Aeration Efficiency of Weirs Using ANN Approach - Baylar, Ahmet; Kisi, Ozgur; Emiroglu, M. Emin (Gazi Univ, 2009)
The concentration of dissolved oxygen is an important indicator of water quality because aquatic life lives on the dissolved oxygen in the water. A free overfall jet from a weir plunging into downstream water causes entrainment of the air bubbles if the free overfall jet velocity exceeds a certain critical value and hence aeration occurs. This paper investigates the free overfall jets from triangular sharp-crested weirs and their effect on the air entrainment rate and the aeration efficiency. The artificial neural network models, multi nonlinear and linear regression equations were obtained for the triangular sharp-crested weirs relating the air entrainment rate and the aeration efficiency to drop height, discharge, and angle in triangular sharp-crested weir. There were good agreements between the measured values and the values obtained using the artificial neural network and multi nonlinear regression models.
Keywords: Air entrainment rate; Aeration efficienc; Dissolved oxygen; Weir; Neural networks